Effect of neural mobilization techniques and nerve mobilization exercise on ulnar nerve entrapment post supracondylar humeral fracture. A case report - Bhat, Ishfaq Bashir (Acta Scientific Publications (OPC) Private Limited, 2020)
Introduction: The purpose of this case report is to describe the role of ulnar nerve mobilization techniques on post humeral fracture entrapment of ulnar nerve in and around the healing fracture. Ulnar nerve entrapment is the second most of entrapment neuropathy in upper limb. Ulnar nerve can get entrapped in callus in supracondylar fracture. Case Description: A 22‐year‐old male student presented to physical therapy, progressing well following supracondylar humeral frac‐ ture, sustained 8 weeks prior. During the treatment, the patient reported restricted range of motion and function, with pain. Based on signs and symptoms the patient was having ulnar nerve entrapment. Results/Outcome: After two weeks of manual therapy (ulnar nerve gliding techniques), and a detailed home exercise program (nerve mobilization exercises and ROM), the patient returned to his normal. There was significant improvement in pain (VAS) and the post treatment McGowan score improved from grade 1 to grade 0. There was improvement in patient’s functions the patient specific functional scale (PSF) score improved from 6 to 1. Conclusion: This case report describes the effect of neural mobilization techniques in improving ulnar nerve entrapment post supra‐ condylar fracture of humerus. The case report de